Regulation of S1PR2 by the EBV oncogene LMP1 in aggressive ABC‐subtype diffuse large B‐cell lymphoma. Issue 2 (22nd March 2019) - Vockerodt, Martina; Vrzalikova, Katerina; Ibrahim, Maha; Nagy, Eszter; Margielewska, Sandra; Hollows, Robert; Lupino, Lauren; Tooze, Reuben; Care, Matthew; Simmons, William; Schrader, Alexandra; Perry, Tracey; et al.
Abstract: The Epstein–Barr virus (EBV) is found almost exclusively in the activated B‐cell (ABC) subtype of diffuse large B‐cell lymphoma (DLBCL), yet its contribution to this tumour remains poorly understood. We have focused on the EBV‐encoded latent membrane protein‐1 (LMP1), a constitutively activated CD40 homologue expressed in almost all EBV‐positive DLBCLs and which can disrupt germinal centre (GC) formation and drive lymphomagenesis in mice. Comparison of the transcriptional changes that follow LMP1 expression with those that follow transient CD40 signalling in human GC B cells enabled us to define pathogenic targets of LMP1 aberrantly expressed in ABC‐DLBCL. These included the down‐regulation of S1PR2, a sphingosine‐1‐phosphate (S1P) receptor that is transcriptionally down‐regulated in ABC‐DLBCL, and when genetically ablated leads to DLBCL in mice. Consistent with this, we found that LMP1‐expressing primary ABC‐DLBCLs were significantly more likely to lack S1PR2 expression than were LMP1‐negative tumours. Furthermore, we showed that the down‐regulation of S1PR2 by LMP1 drives a signalling loop leading to constitutive activation of the phosphatidylinositol‐3‐kinase (PI3‐K) pathway. Finally, core LMP1‐PI3‐K targets were enriched for lymphoma‐related transcription factors and genes associated with shorter overall survival in patients with ABC‐DLBCL. Our data identify a novel function for LMP1 in aggressive DLBCL. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.